Reforming the Examination System of Tribhuvan University: Strategies for Enhancing Efficiency and Accountability - Sherpa, Dawa; Khanal, Shanti Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
The Office of the Controller of the Examinations (OCE) of Tribhuvan University (TU), Nepal, is maintaining academic integrity, ensuring fair assessments. This paper aims to explore the strategies for enhancing the efficiency and accountability of the OCE. An interpretive phenomenological research design has been adopted to gather information from the five former deputy controllers of the OCE were purposively selected as participants. An in-depth interview was conducted with semi-structured interview guidelines. The study found that enhancing transparency and accountability, building institutional capacity, and safeguarding the integrity of assessments, timely examination, and result publication, as well as the timely issuance of original and provisional certificates, transcripts, registration cards, and migration certificates to students, are the major challenges of the OCE TU. Moreover, a strategy for the transformation of the OCE was found, delivering an efficient, timely, secure, and student-friendly examination system, implementing an academic calendar. Conferencing/centre-based answer sheet checking system, digitalization of examination system using OCE apps, OCE automation system for examination services, delegating authority, and empowering regional offices enhance the examination system. Ensuring efficiency and accountability, establishing an innovation and research unit inside the OCE, and implementing the findings would be crucial for transforming the examination controller office.